Clinical Scaleup of Humanized AnnA1 Antibody Yielded Unexpected High Reticuloendothelial (RES) Uptake in Mice - Lu Lucy Xu; Satyendra Kumar Singh; Chelsea Nayback; Abdullah Metebi; Dalen Agnew; Tim Buss; Jan Schnitzer; Kurt R. Zinn (Antibodies)
Background/Objectives: A mouse antibody directed against truncated Annexin A1 showed high tumor retention in pre-clinical cancer models and was approved by the National Cancer Institute Experimental Therapeutics (NExT) program for humanization and large batch cGMP production for toxicology and clinical trials. In this process, a contractor for Leidos accidentally produced a mutated version of humanized AnnA1 (hAnnA1-mut) with a single nucleotide deletion in the terminal Fc coding region that increased the translated size by eight amino acids with random alterations in the final twenty-four amino acids. We investigated the tissue distribution of hAnnA1-mut, hAnnA1, mAnnA1, and isotope-matched human IgG1 under various injection and conjugation conditions with C57BL/6, FVB, and BALB/c nude mice strains. Methods: Biodistribution studies were performed 24 h after injection of Tc-99m-HYNIC radiolabeled antibodies (purity > 98%). Non-reducing gel electrophoresis studies were conducted with IR680 labeled antibodies incubated with various mouse sera. Results: Our results showed that Tc-99m-HYNIC-hAnnA1 had low spleen and liver retention not statistically different from Tc-99m-HYNIC-IgG1 and Tc-99m-HYNIC-mAnnA1, with corresponding higher blood levels; however, Tc-99m-HYNIC-hAnnA1-mut had high levels in the spleen and liver with differences identified among the mouse strains, radiolabeling conditions, and injection routes. Histopathology showed no morphological change in the liver or spleen from any conditions. Gel electrophoresis showed an upward shift of hAnnA1-mut, consistent with the binding of blood serum protein. Conclusions: The changes in the Fc region of hAnnA1-mut led to higher liver and spleen uptake, suggesting the antibody’s recognition by the innate immune system (likely complement protein binding) and subsequent clearance. Future clinical translation using hAnnA1 and other antibodies needs to limit protein modifications that could drastically reduce blood clearance.